Pengelolaan Pembelajaran Sains Kelas IV SD Muhammadiyah Alam Surya Mentari Surakarta - Agustiningsih, Yhuanita; , Prof. Dr. Markhamah, M.Hum; , Dr. Sofyan Anif, M.Si (2015)
This study aims to describe the implementation of management science teaching fourth grade Alam Surya Mentari Muhammadiyah Surakarta, include (1) learning materials science (2) the interaction of science learning, (3) evaluation of learning science. This type of qualitative research took place in SD Muhammadiyah Surakarta Mentari Alam Surya. Data collection technique used observation, documentation, and interviews. Sources of data obtained from informants, events and documents. The data were analyzed by analysis interactive model that includes data collection, data reduction, data presentation and conclusion. The results showed that (1) an elementary school teacher Muhammadiyah Surakarta Mentari Alam Surya prosecuted in the mastery, understanding learning materials science and manufacturing of the worksheet as an important part of the learning process to achieve learning objectives. Worksheets prepared by teachers from a variety of learning resources that includes the competence standard, basic competence, learning materials, and exercises for each meeting learning. Teachers in school universe utilizing the natural environment as a learning resource materials and real to the students as the implementation of contextual learning (contextual teaching and learning) (2) The interaction of science learning in SD Muhammadiyah Surakarta Mentari Alam Surya designed multidirectional, fun and educative. Students learn through direct interaction with the object or objects that exist in nature around that assist teachers in the delivery of materials to build the concept of direct learning and real to students (3) Evaluation of science learning fourth grade students of SD Muhammadiyah Alam Surya Mentari Surakarta embodied in a qualitative assessment is by narrative statement in words (typical report cards SD Muhammadiyah Surakarta Mentari Alam Surya) and quantitative assessment in the form of numbers or scores (report cards Muhammadiyah foundation).